The Short-Term Effects of School Consolidation on Student Achievement: Evidence of Disruption? - Louise Voldby Beuchert; Maria Knoth Humlum; Helena Skyt Nielsen; Nina Smith (Institute for the Study of Labor (IZA), 2016)
We exploit variation stemming from school consolidations in Denmark from 2010- 2011 to analyze the impact on student achievement as measured by test scores. For each student we observe enrollment and test scores one year prior to school consolidation and up to four years after. We find that school consolidation has adverse effects on achievement in the short run and that these effects are most pronounced for students exposed to school closings. Furthermore, students initially enrolled in small schools experience the most detrimental effects. The effects appear to weaken over time, suggesting that part of the effect is due to disruption.
Keywords: I21; J24; 330; school size; school resources; disruption effects; educational production function; test scores